2004
DOI: 10.1108/09578230410534667
|View full text |Cite
|
Sign up to set email alerts
|

Relation of principal transformational leadership to school staff job satisfaction, staff turnover, and school performance

Abstract: In the present study, the direct effect of principal transformational leadership to school staff turnover and school performance was examined, in addition to its indirect effect through school staff job satisfaction. Survey data were obtained from elementary school staff and students, and school-aggregated student achievement test scores were obtained from school archives. Results showed that staff reports of principal behaviors could be described in terms of the three components of transformational leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
265
2
28

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(328 citation statements)
references
References 46 publications
33
265
2
28
Order By: Relevance
“…Several studies supported the effect of principal's leadership behaviours on teachers' job satisfaction (Dinham & Scott, 1998;Bogler, 2001;Griffith, 2004;Nguni et al, 2006;Cerit, 2009). Studies proved that the principal's leadership behaviour is one of the positive factors that have a direct correlation with teachers' job satisfaction (Bogler, 2001).…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies supported the effect of principal's leadership behaviours on teachers' job satisfaction (Dinham & Scott, 1998;Bogler, 2001;Griffith, 2004;Nguni et al, 2006;Cerit, 2009). Studies proved that the principal's leadership behaviour is one of the positive factors that have a direct correlation with teachers' job satisfaction (Bogler, 2001).…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 88%
“…Studies proved that the principal's leadership behaviour is one of the positive factors that have a direct correlation with teachers' job satisfaction (Bogler, 2001). Considerable research has been carried out on the influence and impact of principal's leadership behaviour on teachers' job satisfaction (Griffith, 2004;Stockard & Lehman, 2004;Cerit, 2009). Furthermore, studies also indicated that principal's decision-making style influences teachers' job satisfaction.…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 99%
“…After 1999, studies have been based on the examination of relationship between transformational leadership and numerous variables and showed that this style has positive impact on: satisfaction (Griffith, 2004;Leithwood & Jantzi, 2008;Bolger, 2001) motivation (Griffith, 2004;Kruger, Witziers & Sleegers, 2007), commitment (Geijsel, et. al., 2003;Yu, et.…”
Section: Researches Of Transformational School Leadershipmentioning
confidence: 99%
“…This raises an important question about principal selection in leading the schools and the importance of developing a team that can work together to achieve the outcomes. Transformational leaders are those who can facilitate change and inspire others to excel (Bass & Riggio, 2006;Griffith, 2004;Rao, 2014). Therefore, a holistic study about effective teaching, learning, and leadership will explicate more factors about effective turnaround methods.…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
“…Essentially, an employee's commitment to an organization that extends beyond basic job satisfaction and traditional loyalty to the employer is influenced by leadership style. Griffith (2004) established a relationship between transformational leadership in schools and teacher satisfaction in his study "Relation of Principal Transformational…”
Section: Framework For the Studymentioning
confidence: 99%